Quasistatic computer simulations of shear behavior of water nanoconfined between mica surfaces - Fedyanin, Ivan; Pertsin, Alexander; Grunze, Michael (The journal of chemical physics, 2011)
We combine the grand canonical Monte Carlo and molecular dynamics techniques to simulate the shear response of water under a 9.2 Å confinement between two parallel sheets of muscovite mica. The shear deformation is modeled in the quasistatic regime corresponding to an infinitely small shear rate. It is found that the confined water film is capable of sustaining shear stress, as is characteristic of solids, while remaining fluid-like in respect of molecular mobility and lateral order. An important information is obtained by splitting the stress tensor components into contributions arising from the interaction of the opposing mica sheets between themselves and their interaction with water. The mica-mica contributions to shear stress show a strong anisotropy dictated by the alignment of the surface K+ ions in chains along the x axis. On shearing in this direction, the mica-mica contribution to shear stress is negligible, so that the shear resistance is determined by the water interlayer. By contrast, in the y direction, the mica-mica contribution to shear resistance is dominant. The water-mica contribution is slightly less in magnitude but opposite in sign. As a consequence, the mica-mica contribution is largely canceled out. The physics behind this cancellation is the screening of the electrostatic interactions of the opposing surface K+ ions by water molecules.
Gesehen am 03.05.2022